2016
DOI: 10.3892/ijmm.2016.2651
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of and in vitro and in vivo evaluation of a novel TGF-β1-SF-CS three-dimensional scaffold for bone tissue engineering

Abstract: The role of transforming growth factor-β1 (TGF-β1) in normal human fracture healing has been previously demonstrated. The objective of the present study was to examine the biocompatibility of TGF-β1-silk fibroin-chitosan (TGF-β1-SF-CS) three-dimensional (3D) scaffolds in order to construct an ideal scaffold for bone tissue engineering. We added TGF-β1 directly to the SF-CS scaffold to construct a 3D scaffold for the first time, to the best of our knowledge, and performed evaluations to determine whether it may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 56 publications
0
18
1
Order By: Relevance
“…The solutions were poured into Teflon culture plates and lyophilized (Alpha 1-2 LD plus, Christ, Germany) for 72 h to obtain nHACM scaffolds. After a series of scaffold evaluations, BMP-9 (500ng/ml) was loaded into the scaffolds when the solution was stirred before freeze drying [23, 24] (Supplementary Figure A). We found that the most appropriate proportion of MWCNTs was 1% for bone tissue engineering in a preliminary experiment (Supplementary Figure B).…”
Section: Methodsmentioning
confidence: 99%
“…The solutions were poured into Teflon culture plates and lyophilized (Alpha 1-2 LD plus, Christ, Germany) for 72 h to obtain nHACM scaffolds. After a series of scaffold evaluations, BMP-9 (500ng/ml) was loaded into the scaffolds when the solution was stirred before freeze drying [23, 24] (Supplementary Figure A). We found that the most appropriate proportion of MWCNTs was 1% for bone tissue engineering in a preliminary experiment (Supplementary Figure B).…”
Section: Methodsmentioning
confidence: 99%
“…Macroscopic analysis of mice skin lesions, treatment using saline (negative control), collagenase (ABBOTT, Chicago, IL, USA) (positive control), pure gels, and oil-associated gel revealed the evolution of wound tissue repair with hemorrhage in the treated groups with SF, PC, and CG on the third and seventh day of treatment. This is detrimental to healing because it can compromise cell proliferation and promote bacterial growth [44,45].…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…Allografting could overcome these limitations, but it is associated with the risk of infectious diseases, an insufficient number of donors and high costs (Greenwald et al 2012). Recombinant growth factors, cell-based engineered bone substitutes and commercial scaffolds are sophisticated alternatives which are widely accepted in the developed world but are too expensive for patients in the low-income countries (Mao and Mooney 2015; Tollemar et al 2016; Tong et al 2016a, b). Recently, the interest in the development of scaffolds from naturally available and low-cost bioactive materials has increased significantly (Baino et al 2015; Yi et al 2016).…”
Section: Introductionmentioning
confidence: 99%